Contextualising Maximal Fat Oxidation During Exercise: Determinants and Normative Values - Maunder, Ed; Plews, Daniel J.; Kilding, Andrew E. (Frontiers in Physiology, 2018)
Using a short-duration step protocol and continuous indirect calorimetry, whole-body rates of fat and carbohydrate oxidation can be estimated across a range of exercise workloads, along with the individual maximal rate of fat oxidation (MFO) and the exercise intensity at which MFO occurs (Fatmax). These variables appear to have implications both in sport and health contexts. After discussion of the key determinants of MFO and Fatmax that must be considered during laboratory measurement, the present review sought to synthesise existing data in order to contextualise individually measured fat oxidation values. Data collected in homogenous cohorts on cycle ergometers after an overnight fast was synthesised to produce normative values in given subject populations. These normative values might be used to contextualise individual measurements and define research cohorts according their capacity for fat oxidation during exercise. Pertinent directions for future research were identified.